Sensory representations in the striatum provide a temporal reference for learning and executing motor habits - Ana E. Hidalgo-Balbuena (Nature Portfolio, 2019)
The authors combine anatomical mapping, electrophysiological recordings, lesions, and pharmacological and optogenetic manipulations in rats to examine the role of forelimb somatosensory flow in the dorsolateral striatum in the learning and execution of motor habits.